KEJADIAN STUNTING DENGAN KEMAMPUAN KOGNITIF ANAK USIA SEKOLAH - Marthalena Simamora; Rosetty Sipayung; Janno Sinaga; Anisa Amanda Sutrisna (Jurnal Online Keperawatan Indonesia, 2023)
compared to children their age. Stunting can cause children to experience brain development disorders. Studies have found that stuntesd children have lower cognitive abilities and poorer school performance. The impact of child stunting is often associated with lowerintelligence at school age. Cognitive can be defined as the ability to learn new skills and concepts, the ability to understand what is happening in the environment, and the skills to use memory and solve simple problems. The purpose of this study was to determine the relationship between the incidence of stunting and the cognitive abilities of school-age children in Percut Sei Tuan Village. This type of research is cross sectional. The population in this research sample of 107 school-age children was taken using random sampling so that the total sample was 51 school-age children. Data collection through measurement of height, weight and questionnaires. Analysis using chi-square. The results showed that the frequency of stunting was the majority experienced stuntingas much as 82.4% and the frequency of cognitive abilities of the majority experienced moderate cognitive impairment was 68.6% and there was a relationship between the incidence of stunting and the cognitive abilities of school-age children with p-value0.031. Based on the results of this study,it is suggested that the role of the mother plays a very important role in the nutrition and development of children.